Resistin in rheumatoid arthritis synovial tissue, synovial fluid and serum - Senolt, L; Housa, D; Vernerová, Z; Jirásek, T; Svobodová, R; Veigl, D; Anderlová, K; Müller-Ladner, U; Pavelka, K; Haluzík, M (Annals of the rheumatic diseases, 2007)
BACKGROUND: Resistin is a newly identified adipocytokine which has demonstrated links between obesity and insulin resistance in rodents. In humans, proinflammatory properties of resistin are superior to its insulin resistance-inducing effects. OBJECTIVES: To assess resistin expression in synovial tissues, serum and synovial fluid from patients with rheumatoid arthritis, osteoarthritis and spondylarthropathies (SpA), and to study its relationship with inflammatory status and rheumatoid arthritis disease activity. METHODS: Resistin expression and localisation in synovial tissue was determined by immunohistochemistry and confocal microscopy. Serum and synovial fluid resistin, leptin, interleukin (IL)1beta, IL6, IL8, tumour necrosis factor alpha, and monocyte chemoattractant protein-1 levels were measured. The clinical activity of patients with rheumatoid arthritis was assessed according to the 28 joint count Disease Activity Score (DAS28). RESULTS: Resistin was detected in the synovium in both rheumatoid arthritis and osteoarthritis. Staining in the sublining layer was more intensive in patients with rheumatoid arthritis compared with those with osteoarthritis. In rheumatoid arthritis, macrophages (CD68), B lymphocytes (CD20) and plasma cells (CD138) but not T lymphocytes (CD3) showed colocalisation with resistin. Synovial fluid resistin was higher in patients with rheumatoid arthritis than in those with SpA or osteoarthritis (both p<0.001). In patients with rheumatoid arthritis and SpA, serum resistin levels were higher than those with osteoarthritis (p<0.01). Increased serum resistin in patients with rheumatoid arthritis correlated with both CRP (r=0.53, p<0.02), and DAS28 (r=0.44, p<0.05), but not with selected (adipo) cytokines. CONCLUSION: The upregulated resistin at local sites of inflammation and the link between serum resistin, inflammation and disease activity suggest a role for resistin in the pathogenesis of rheumatoid arthritis.
Keywords: Female; Severity of Illness Index; lidé středního věku; biologické markery; revmatoidní artritida; mužské pohlaví; Arthritis, Rheumatoid; Synovial Fluid; Humans; dospělí; Immunoenzyme Techniques; konfokální mikroskopie; spondylartropatie; stupeň závažnosti nemoci; Inflammation Mediators; artróza kolenních kloubů; synoviální membrána; synoviální tekutina; Resistin; lidé; Middle Aged; imunoenzymatické techniky; Synovial Membrane; senioři; ženské pohlaví; resistin; Aged; Spondylarthropathies; Adult; Biomarkers; mediátory zánětu; Osteoarthritis, Knee; Male; Microscopy, Confocal